Imaging of cAMP levels and protein kinase A activity reveals that retinal waves drive oscillations in second-messenger cascades. - Dunn, T; Wang, C; Colicos, M; Zaccolo, M; DiPilato, L; Zhang, J; Tsien, R; Feller, M (2006)
Recent evidence demonstrates that low-frequency oscillations of intracellular calcium on timescales of seconds to minutes drive distinct aspects of neuronal development, but the mechanisms by which these calcium transients are coupled to signaling cascades are not well understood. Here we test the hypothesis that spontaneous electrical activity activates protein kinase A (PKA). We use live-cell indicators to observe spontaneous and evoked changes in cAMP levels and PKA activity in developing retinal neurons. Expression of cAMP and PKA indicators in neonatal rat retinal explants reveals spontaneous oscillations in PKA activity that are temporally correlated with spontaneous depolarizations associated with retinal waves. In response to short applications of forskolin, dopamine, or high-potassium concentration, we image an increase in cAMP levels and PKA activity, indicating that this second-messenger pathway can be activated quickly by neural activity. Depolarization-evoked increases in PKA activity were blocked by the removal of extracellular calcium, indicating that they are mediated by a calcium-dependent mechanism. These findings demonstrate for the first time that spontaneous activity in developing circuits is correlated with activation of the cAMP/PKA pathway and that PKA activity is turned on and off on the timescale of tens of seconds. These results show a link between neural activity and an intracellular biochemical cascade associated with plasticity, axon guidance, and neural differentiation.